Entransy Dissipation of Shell and Double Concentric Tubes Heat Exchanger - Abdulmajeed, Basma Abbas; Abdulah, Zena Fallah (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The concept of entransy dissipation was determined for new type of heat exchanger (shell and double concentric tubes heat exchanger). Three parameters, hot oil flow rate, temperature of inlet hot oil and pressure drop of system were investigated with this concept (entransy dissipation). The results showed that the value of entransy dissipation of oil and of system which represents the summation of entransy dissipation of both oil and water increased with increasing the flow rate of hot oil and these values were larger when cold water flow rate was doubled. Also they were increased with increasing the hot oil inlet temperature at a certain flow rate of hot oil. Furthermore, the pressure drops for hot oil in both shell side and inner tubes side was constant and increased according to the increase of its flow rate. At different hot oil flow rate and a certain hot oil inlet temperature, the entransy of hot oil was increased with its pressure drop. In order to keep up with modern technology, infrared thermography camera was used in order to measure the temperatures which were higher than the temperatures obtained by thermocouples. For that reason the entransy dissipation was determined with lower values compared with their values obtained by using thermocouples.